EFFECT OF TAX POLICY ON FOREIGN INVESTMENT IN INDONESIA - Kristin, Apriaty; one, Drs. Supardi, MM. (Accounting, 2009)
The purpose of this research to know bangaimana policy influence tax legislation in foreign investment in Indonesia. Research conducted on the development of the realization of investment in Indonesia and taxation policies such as Government Regulation No. 1 of 2007. Technical analysis of test data with Comparison to the realization of development data INDONESIA Investment. And the results have the effect of tax policy on foreign investment in Indonesia before and after the policy issued in 2007. The results showed no significant difference in the average before and after implementation of government regulation. 1 of 2007. Keywords : tax policy, foreign investment